A Comparative Analysis of Remedies and Challenges in the Protection of Stakeholders Rights: OHADA vs. English Corporate Law - Dr. Nchofua Anita Nyitioseh (Studies in Law and Justice, 2024)
This article provides a comparative analysis of the remedies and challenges in the protection of stakeholder rights under OHADA (Organization for the Harmonization of Business Law in Africa) and English corporate law. The study focuses on key legal remedies available to stakeholders, including the derivative action model, the unfair prejudice remedy, personal right of action, remedies for breach of contract and torts, representative actions amongst other remedies. Under OHADA, the uniform legal framework aims to harmonize business laws across member states, promoting legal certainty and economic growth. In this context, the derivative action model allows minority shareholders to seek redress for wrongs committed against the company, while the unfair prejudice remedy protects stakeholders from actions that harm their interests. Personal right of action and remedies for breach of contract and torts provide additional avenues for stakeholders to seek justice. Representative actions further enable collective redress for affected parties. In contrast, English corporate law, rooted in a common law tradition, offers flexibility and judicial interpretation in protecting stakeholder rights. The derivative action model in English law allows shareholders to bring claims on behalf of the company, while the unfair prejudice remedy addresses situations where minority shareholders are treated unfairly. Personal right of action and remedies for breach of contract and torts are well-established, providing robust protection for stakeholders. Representative actions in English law facilitate collective litigation, enhancing access to justice. In tandem with the foregoing, this paper explores challenges in the practical enforcement of these remedies, including differences in legal culture, enforcement mechanisms, and jurisdictional issues. By comparing OHADA and English corporate law, the study provides insights into the effectiveness of various legal frameworks in protecting stakeholder rights and offers recommendations for enhancing stakeholder protection through legal reforms and policy initiatives. Through a content analysis of primary and secondary data, we uphold that this article contributes to the discourse on corporate governance and stakeholder theory, offering valuable perspectives for policymakers, legal practitioners, and scholars interested in the protection of stakeholder rights in diverse legal environments.